2021
DOI: 10.1038/s41531-021-00223-5
|View full text |Cite
|
Sign up to set email alerts
|

Subthalamic and pallidal deep brain stimulation for Parkinson’s disease—meta-analysis of outcomes

Abstract: Although deep brain stimulation (DBS) of the globus pallidus internus (GPi) and the subthalamic nucleus (STN) has become an established treatment for Parkinson’s disease (PD), a recent meta-analysis of outcomes is lacking. To address this gap, we performed a meta-analysis of bilateral STN- and GPi-DBS studies published from 1990-08/2019. Studies with ≥10 subjects reporting Unified Parkinson’s Disease Rating Scale (UPDRS) III motor scores at baseline and 6–12 months follow-up were included. Several outcome vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 83 publications
2
66
0
Order By: Relevance
“…Two additional trials compared GPi‐DBS and STN‐DBS without a BMT arm and found no differences in changes of primary outcome measures 16,17 . However, both showed greater levodopa equivalent dose reductions and one showed greater improvements in off medication motor functioning with STN‐DBS, 16 findings that were confirmed by a recent large meta‐analysis 18 . Based on this solid evidence STN‐DBS and GPi‐DBS are firmly established treatment modalities to improve motor fluctuations and dyskinesias in advanced PD 19 .…”
Section: Deuschl Et Al9 Williams Et Al10 (Pd Surg) Weaver Et Al12 O...mentioning
confidence: 85%
See 1 more Smart Citation
“…Two additional trials compared GPi‐DBS and STN‐DBS without a BMT arm and found no differences in changes of primary outcome measures 16,17 . However, both showed greater levodopa equivalent dose reductions and one showed greater improvements in off medication motor functioning with STN‐DBS, 16 findings that were confirmed by a recent large meta‐analysis 18 . Based on this solid evidence STN‐DBS and GPi‐DBS are firmly established treatment modalities to improve motor fluctuations and dyskinesias in advanced PD 19 .…”
Section: Deuschl Et Al9 Williams Et Al10 (Pd Surg) Weaver Et Al12 O...mentioning
confidence: 85%
“…16,17 However, both showed greater levodopa equivalent dose reductions and one showed greater improvements in off medication motor functioning with STN-DBS, 16 findings that were confirmed by a recent large meta-analysis. 18 Based on this solid evidence STN-DBS and GPi-DBS are firmly established treatment modalities to improve motor fluctuations and dyskinesias in advanced PD. 19 STN-DBS is also highly efficacious in reducing or even abolishing drug refractory PD tremor and is widely used in clinical practice for this indication.…”
mentioning
confidence: 96%
“…The globus pallidus internus (Gpi) is an alternative DBS target for PD patients besides STN implantation as the Gpi is supposed to have a lower risk of dysarthria, neuropsychiatric complications and impaired cognition [ 61 ]. The discussion of the favorable target in PD is still controversial [ 61 ]. There is also scarce information on caregiver burden in Gpi patients [ 31 , 62 ].…”
Section: Caregiver Burden In Pd Patients With Globus Pallidus Internu...mentioning
confidence: 99%
“…On the other hand, although it seems relatively safe concerning cognitive function, chronic stimulation of STN has been associated with a subtle decline in cognitive domains, exceptionally verbal fluency, and executive function [90,91]. Despite little data is supporting that STN-DBS has a worse cognitive outcome than GPi-DBS [92], more published information is required for validation [93]; if there is significant concern about cognitive decline, particularly regarding verbal fluency, processing speed, and working memory in a patient undergoing DBS, GPi has been recommended [84,89].…”
Section: Dbs In Carriers Of Genetic Variants That Modify the Risk For...mentioning
confidence: 99%